A systematic review and meta-analysis of the overall effects of school-based obesity prevention interventions and effect differences by intervention components - Zheng Liu; Han-Meng Xu; Li-Ming Wen; Yuan-Zhou Peng; Li-Zi Lin; Shuang Zhou; Wen-Hao Li; Hai-Jun Wang (BMC, 2019)
Abstract Background Childhood obesity is a serious public health concern. School-based interventions hold great promise to combat the rising trend of childhood obesity. This systematic review aimed to assess the overall effects of school-based obesity prevention interventions, and to investigate characteristics of intervention components that are potentially effective for preventing childhood obesity. Methods We systematically searched MEDLINE, CENTRAL and Embase databases to identify randomized- or cluster randomized- controlled trials of school-based obesity interventions published between 1990 and 2019. We conducted meta-analyses and subgroup analyses to determine the overall effects of obesity prevention programs and effect differences by various characteristics of intervention components on body mass index (BMI) or BMI Z-score of children. Results This systematic review included a total of 50 trials (reported by 56 publications). Significant differences were found between groups on BMI (− 0.14 kg/m2 (95% confidence interval: − 0.21, − 0.06)) and BMI Z-score (− 0.05 (− 0.10, − 0.01)) for single-component interventions; significant differences were also found between groups on BMI (− 0.32 (− 0.54, − 0.09) kg/m2) and BMI Z-score (− 0.07 (− 0.14, − 0.001)) for multi-component interventions. Subgroup analyses consistently demonstrated that effects of single-component (physical activity) interventions including curricular sessions (− 0.30 (− 0.51, − 0.10) kg/m2 in BMI) were stronger than those without curricular sessions (− 0.04 (− 0.17, 0.09) kg/m2 in BMI); effects of single-component (physical activity) interventions were also strengthened if physical activity sessions emphasized participants' enjoyment (− 0.19 (− 0.33, − 0.05) kg/m2 in BMI for those emphasizing participants' enjoyment; − 0.004 (− 0.10, 0.09) kg/m2 in BMI for those not emphasizing participants' enjoyment). The current body of evidence did not find specific characteristics of intervention components that were consistently associated with improved efficacy for multi-component interventions (P > 0.05). Conclusions School-based interventions are generally effective in reducing excessive weight gain of children. Our findings contribute to increased understandings of potentially effective intervention characteristics for single-component (physical activity) interventions. The impact of combined components on effectiveness of multi-component interventions should be the topic of further research. More high-quality studies are also needed to confirm findings of this review.